Apparatus for studying electro-physical properties of materials at low temperatures under external magnetic fields - Bovda, O.M.; Derevyanko, V.V.; Sukhareva, T.V.; Finkel, V.A. (Functional Materials, 2014)
The object of the work is development and experimental realization of the apparatus for measuring electro-physical properties of materials at temperatures 15-273 K in external magnetic field Hext; in the apparatus, a gas heat engine (cryo-generator) has been used for obtaining low temperatures, and a system of permanent magnets has been applied for producing magnetic fields with magnetization force up to several kOe. Actually, the apparatus consists of two large blocks: a stationary setup for producing low temperatures using the cryo-generator (Leybold), and a detachable setup for creating magnetic fields using a system of permanent magnets pairs made from high-coercive Nd₂Fe₁₄B alloy. A system for collecting and treating the data obtained has been developed. For testing the apparatus, comparative measurements of electrical resistivity temperature dependence for MgB₂ superconductor have been carried out both in zero magnetic field and under Hext = 2 kOe.